2013
DOI: 10.1371/journal.pone.0054459
|View full text |Cite
|
Sign up to set email alerts
|

Pentosan Polysulfate: A Novel Therapy for the Mucopolysaccharidoses

Abstract: BackgroundPentosan polysulfate (PPS) is an FDA-approved, oral medication with anti-inflammatory and pro-chondrogenic properties. We have previously shown that animal models of the mucopolysaccharidoses (MPS) exhibit significant inflammatory disease, contributing to cartilage degeneration. Enzyme replacement therapy (ERT) only partly reduced inflammation, and anti-TNF-alpha antibody therapy significantly enhanced clinical and pathological outcomes. Here we describe the use of PPS for the treatment of MPS type V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
85
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 39 publications
(52 reference statements)
9
85
1
1
Order By: Relevance
“…Schuchman et al also reported that oral and subcutaneous administration of PPS reduced inflammation and improved skeletal pathology, bone mineral density, and mobility of joints in MPS VI rats [39,139,140]. Ghosh et al reported that PPS promotes proliferation, and chondrogenic differentiation of adult human bone marrow-derived mesenchymal precursor cells [139]. In our preliminary experiment, PPS suppressed GAG accumulation in fibroblasts of several types of MPS patients.…”
Section: Anti-inflammatory Drugssupporting
confidence: 61%
See 2 more Smart Citations
“…Schuchman et al also reported that oral and subcutaneous administration of PPS reduced inflammation and improved skeletal pathology, bone mineral density, and mobility of joints in MPS VI rats [39,139,140]. Ghosh et al reported that PPS promotes proliferation, and chondrogenic differentiation of adult human bone marrow-derived mesenchymal precursor cells [139]. In our preliminary experiment, PPS suppressed GAG accumulation in fibroblasts of several types of MPS patients.…”
Section: Anti-inflammatory Drugssupporting
confidence: 61%
“…Successively, clinical trials of PPS in patients with knee osteoarthritis provided significant reduction in pain [138]. Schuchman et al also reported that oral and subcutaneous administration of PPS reduced inflammation and improved skeletal pathology, bone mineral density, and mobility of joints in MPS VI rats [39,139,140]. Ghosh et al reported that PPS promotes proliferation, and chondrogenic differentiation of adult human bone marrow-derived mesenchymal precursor cells [139].…”
Section: Anti-inflammatory Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzyme replacement therapy (ERT) [3][4][5], hematopoietic stem cell transplantation (HSCT) [6][7][8][9], substrate reduction therapy (SRT) [10,11], gene therapy [12,13], and anti-inflammatory drugs [14,15] are in clinical use or being investigated under clinical trials for patients with some types of MPS. Initiating these treatments at birth or during early stages provides most benefits in the clinical improvement of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Aldouronates, acidic xylooligosaccharides (U-XOS and U-AXOS, where U represents uronate) in which some xylose (X) residues are substituted with ␣-1,2-linked 4-O-methylglucuronate (MeG), have been shown to exhibit anti-inflammatory and other immunomodulating activities (5). These acidic forms comprise a portion of the pentosans that are used for the preparation of pentosan polysulfates (PPSs), which have several medical applications, including the treatment of interstitial cystitis, mucopolysaccharidoses, and osteoarthritis (6)(7)(8). The generation of different forms of XOS and AXOS or U-XOS and U-AXOS results from the depolymerization of both methylglucuronoxylans (MeGX n ) and methylglucuronoarabinoxylans (MeGAX n ), the predominant polymers comprising the hemicellulose fractions of lignocellulosics derived from most species of dicots and monocots, respectively (9,10).…”
mentioning
confidence: 99%